The effect of mobile learning in higher education mathematics. (30th August 2019) - Hakim, L.
Mobile learning (M-learning) is not a virtual library, nor is it a means to replace lectures. It is intended to complement lectures/seminars and harmonises learning techniques by using mobile applications such as phones, PDAs, and tablets. As students become increasingly technophilic, the digital revolution becomes an integral part of education. M-learning is not shifting from PCs to phones, it is a way of extending the hierarchy of learning facilities. M-learning offers new ways for lecturers to deliver material, new ways for students to revise independently and with their peers, and integrates learning into their daily lives. Known for their flexibility, ability to exchange information, popularity, and of course mobility, mobile devices can be a suitable education resource. However, how serious are the drawbacks to M-learning? To what extent is M-learning advancing learning strategies? Does M-learning have any impact on the mindset of students in higher education? In this project, we explore the big questions related to M-learning, with a focus on the Department of Mathematics at the University of Exeter.